HYDROTHERMAL SYNTHESIS OF Ca3Si2O7 AND CaSiO3 AS PHOTOLUMINESCENT MATERIALS - AZHAMY (NIM :10509064) ; Pembimbing Dr. Bambang Prijamboedi, ARIA
White light emitting diode (WLED) is considered as the next generation artificial light source because of its longer lifetime, small form factor and also high energy efficiency. Calcium silicate-based phosphors (CaÃ‚Â–SiÃ‚Â–O/CSO) such as Ca3Si2O7 and CaSiO3 that were usually prepared by solid-state reaction route gave poor crystal homogenity. This research studied the synthesis of Ca3Si2O7 and CaSiO3 through hydrothermal route. Ca(NO3)2 was diluted in aquadest and tetraethyl orthosilicate (TEOS) was diluted in ethylenediamine, then both reagent solutions were mixed thoroughly and reacted inside an autoclave. X-ray diffraction (XRD) pattern of Ca(NO3)2 and TEOS with stoichiometric composition of Ca3Si2O7 that were reacted hydrothermally using 20 mL aquadest + 50 mL ethylenediamine at 190 Ã‚Â°C showed CaCO3 (CCO) and amorphous silica. This was due to the formation of CO32- cation and CSOÃ‚Â’s high thermal stability. Synthesis parameter such as precursor type, solvent volume, synthesis temperature, calcination temperature and duration were varied to achieve Ca3Si2O7 and CaSiO3. Based on XRD patterns, synthesis of Ca3Si2O7 with the highest yield (47.58% volume fraction) was achieved using Ca(NO3)2 and TEOS diluted in 20 mL aquadest + 50 mL ethylenediamine at 190 Ã‚Â°C and was calcined at 1000 Ã‚Â°C for 2 hours. Synthesis of CaSiO3 with the highest yield (72.57% volume fraction) was achieved using Ca(NO3)2 and TEOS diluted in 20 mL aquadest + 50 mL ethylenediamine and calcined at 1200 Ã‚Â°C for 24 hours. Synthesis of Ca0.995SiO3:0.005Eu3+ with yield of 42.52% volume fraction and cell parameters of a = 6.8292 ÃƒÂ…, b = 11.8585 ÃƒÂ…, c = 19.5927 ÃƒÂ… and β = 90.8141Ã‚Â° was achieved using Ca(NO3)2, Eu(NO3)3 and TEOS diluted in 20 mL aquadest + 50 mL ethylenediamine and calcined at 1200 Ã‚Â°C for 24 hours. Crystals formed aggregates and tabular-shaped crystals. Photoluminescence spectra indicated that maximum excitation occurred at 393 nm and highest emission intensity occurred at 611 nm.